A Power Comparison Between Nonparametric Regression Tests - Dette, Holger; Zhang, Chunming (Universitätsbibliothek Dortmund, 2003)
In this paper, we consider three major types of nonparametric regression tests that are based on kernel and local polynomial smoothing techniques. Their asymptotic power comparisons are established systematically under the fixed and contiguous alternatives, and are also illustrated through non-asymptotic investigations and finite-sample simulation studies.
Keywords: goodness-of-fit; local alternative; local polynomial regression; power; smoothing parameter; 310